2017
DOI: 10.4162/nrp.2017.11.2.114
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum carotenoid, retinol, and tocopherol concentrations with the progression of Parkinson's Disease

Abstract: BACKGROUND/OBJECTIVESA pivotal role of oxidative stress has been emphasized in the pathogenesis as well as in the disease progression of Parkinson's disease (PD). We aimed at investigating serum levels of antioxidant vitamins and elucidating whether they could be associated with the pathogenesis and progression of PD.MATERIALS/METHODSSerum levels of retinol, α- and γ-tocopherols, α- and β-carotenes, lutein, lycopene, zeaxanthin and β-cryptoxanthin were measured and compared between 104 patients with idiopathic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 47 publications
(75 reference statements)
1
25
0
Order By: Relevance
“…Twenty-one eligible observational studies were selected, including 13 case-control [10,11,[18][19][20][21][22][23][24][25][26][27][28] and 8 cohort studies [9,[29][30][31][32][33][34][35]. Thirteen case-control studies included 5529 PD patients and 6176 controls.…”
Section: Study Characteristics and Results Of The Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one eligible observational studies were selected, including 13 case-control [10,11,[18][19][20][21][22][23][24][25][26][27][28] and 8 cohort studies [9,[29][30][31][32][33][34][35]. Thirteen case-control studies included 5529 PD patients and 6176 controls.…”
Section: Study Characteristics and Results Of The Quality Assessmentmentioning
confidence: 99%
“…Flow diagram of study selection for the meta-analysis21,23,27]. Other details of the baseline data are shown in…”
mentioning
confidence: 99%
“…To clarify the inconsistencies observed in human studies, a recent systematic review that analyzed pooled data from relevant papers published between 1990 and 2013 raised the possibility that both α - and β -carotene levels might be inversely proportional to PD risk [ 137 ]. Following this systematic study, a very recent paper by Kim et al [ 138 ] reported that the serum levels of some carotenoids ( α -carotene, β -carotene, and lycopene) were significantly lower in PD patients, and that these carotenoids were inversely correlated with clinical variables representing disease progression. On the contrary, another study reported that the consumption of vitamin E and carotenoids was not associated with the risk of PD [ 139 ].…”
Section: Beneficial Effects Of Carotenoids On Neurodegenerative DImentioning
confidence: 86%
“…RA levels in plasma of PD patients are reduced [ 169 ]. PD patients also demonstrate reduced levels of α- and β-carotenes and lycopene in serum, which also inversely correlated with motor part of UPDRS scores and Hoehn and Yahr stage [ 170 ].…”
Section: Candidate Biomarkers For Oxidative Stress In Parkinson’s mentioning
confidence: 99%